Oral administration of a synthetic vinyl-ether plasmalogen normalizes open field activity in a mouse model of rhizomelic chondrodysplasia punctata - Wedad Fallatah; Tara Smith; Wei Cui; Dushmanthi Jayasinghe; Erminia Di Pietro; Shawn A. Ritchie; Nancy Braverman (The Company of Biologists, 2020)
Rhizomelic chondrodysplasia punctata (RCDP) is a rare genetic disorder caused by mutations in peroxisomal genes essential for plasmalogen biosynthesis. Plasmalogens are a class of membrane glycerophospholipids containing a vinyl-ether-linked fatty alcohol at the sn-1 position that affect functions including vesicular transport, membrane protein function and free radical scavenging. A logical rationale for the treatment of RCDP is therefore the therapeutic augmentation of plasmalogens. The objective of this work was to provide a preliminary characterization of a novel vinyl-ether synthetic plasmalogen, PPI-1040, in support of its potential utility as an oral therapeutic option for RCDP. First, wild-type mice were treated with 13C6-labeled PPI-1040, which showed that the sn-1 vinyl-ether and the sn-3 phosphoethanolamine groups remained intact during digestion and absorption. Next, a 4-week treatment of adult plasmalogen-deficient Pex7hypo/null mice with PPI-1040 showed normalization of plasmalogen levels in plasma, and variable increases in plasmalogen levels in erythrocytes and peripheral tissues (liver, small intestine, skeletal muscle and heart). Augmentation was not observed in brain, lung and kidney. Functionally, PPI-1040 treatment normalized the hyperactive behavior observed in the Pex7hypo/null mice as determined by open field test, with a significant inverse correlation between activity and plasma plasmalogen levels. Parallel treatment with an equal amount of ether plasmalogen precursor, PPI-1011, did not effectively augment plasmalogen levels or reduce hyperactivity. Our findings show, for the first time, that a synthetic vinyl-ether plasmalogen is orally bioavailable and can improve plasmalogen levels in an RCDP mouse model. Further exploration of its clinical utility is warranted. This article has an associated First Person interview with the joint first authors of the paper.